From Beowulf to Canterbury Tales: The Evolution of Literary Genres from Old To Middle English - Nafisa, Daania Zahraa; Az Zahro, Daffa Nisrina; Aminullah, Aminullah (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The evolution of literary genres from Old English to Middle English marks, therefore, language, culture, and storytelling tradition changes in England from Anglo-Saxon to later Medieval times. Beowulf is the Old English epic par excellence, and it is steeply integerated within oral-formulaic tradition to have heroic narratives of Germanic legend or pagan value, later Christianized through alliterative verse; it bears witness to the priority of orality within the scops' preserving culturalmemory. The Canterbury Tales, on the other hand, stand as a marker in Middle English literature. It is a collection of 24 tales or stories, all of which represent various kinds, that are told by pilgrims of diverse social classes who travel together to pilgrimage sites. By its use of vernacular Middle English, Chaucer legitimized vernacular Middle English as a literary language that freed it from the domination of Latin and French; nor can we deny its more well-structured narrative, which also takes into account contemporary societal issues, getting influences both from courtly and ecclesiastical traditions. This movement showed the progression from more heroic and oral epics to more complex narratives, and the transition marks an important era in midieval England, showing how changing the language and culture can alter the whole aspect of these developments in literature.